Penyuluhan Gizi Dan Pemberdayaan Ekonomi Perempuan Kelurahan Sindang Barang Bogor - Susanti, Santi; Zulaihati, Sri (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2017)
Good toddlers growth is strongly supported by the fulfillment of nutritional needs. Parents in this case mothers who bond very closely with children are expected to provide and provide nutritious food to their children. Fulfilling children nutrition can not be separated from the economic level of society. Currently there are many families who are not able in economic terms and result in the fulfillment of childhood nutrition becomes a priority for the family. The way that mothers can provide nutritious food is by doing nutritional counseling, on the other hand also need an effort to increase family economic level with craft training so that empowerment of woman in family become optimal. This training is prepared by direct practice simulation method, and at final destination Of this training is the mothers can provide nutritious food for balitanya and economic fulfillment through the training of making brooches that can supplement family income can be done in the spare time